Rotunda of the Senate Building in the Moscow Kremlin: Architectural Graphics and the Iconography of the Project - Yakovlev, Alexey N. (Actual Problems of Theory and History of Art, 2018)
Abstract. The Senate building in the Moscow Kremlin (1776-1787, M. F. Kazakov, with the participation of K. I. Blank) is one of the key monuments in the development of Russian classicism. The study of this architectural object is difficult due to its inaccessibility and the loss of many sources. This study is topical in two aspects: firstly, it was necessary to systematize all the known to date architectural drawings related to the project, construction, and repairs of the building; secondly, an expansion of the analogies of the Senate building in Russian and European architecture of that time was made in order to fit this original building in the architectural context of the Enlightenment. In this study such monuments as the Parliament building in Dublin (1729-1739, Ed. Pearce, 1785-1787, J. Gandon and R. Park); the Capitol in Washington (1792-1827, W. Thornton, B. Latrobe, Ch. Bulfinch) were included in the circle of European and American analogues of the Senate building. Also unrealized projects of the French and Italian schools were analyzed. The iconography of the main hall (domed rotunda) of the Senate hasn’t been specifically analyzed before. Among its analogues there are projects from the albums by J.-F. Neufforge and project of the French Royal Academy of architecture Ch. Maréchaux for the Funerary chapel (1755). However, the closest analogue is the Cathedral of the Monastery of St. Blasien in Schwarzwald (1768-1783, P. M. d’Ixnard).
Keywords: architecture; Classicism; foreign impact; prototype & copy; typology; rotunda; centric building; Matvei Kazakov; Jean-François Nuefforge; Charles Maréchaux; Pierre Michel d’Ixnard